Impact Of Religious Activities On Quality Of Life And Cognitive Function Among Elderly. - Syazwan Nazri Amir; Norsham Juliana; Sahar Azmani; Izuddin Fahmy Abu; Abd Hafiz Qayyum Abd Talib; Farahin Abdullah; Intan Zulaikha Salehuddin; Nur Islami Mohd Fahmi Teng; Nur Azma Amin; Nor Amira Syahira Mohd Azmi; Nur Adilah Shuhada Abd Aziz (Springer Nature, 2024)
Indexed by WOS/Scopus/ERA